Satellite imagery as an alternative to collect data through surveys - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
This study has proposed a methodology to generate maps for rice zones which detailed the crop growth stages. The methodology has generated 3 rice maps that have been validated with farmers. Fedearroz is now using this information to make better agricultural decisions.